Drug testing and productivity - Caste, Nicholas J. (Journal of business ethics, 1992)
In this article I attempt to examine the justification for the mandatory drug testing of employees. The justification commonly assumes the form of the “productivity argument” which states that an employer has a proprietary right to regulate the purchased time of the employee. Since the employer may be rightfully concerned with the employee's productive output, so this argument goes, the employer retains the right to motivate production. By extension, the employee's behavior outside of the workplace which affects his or her productive capacity may also be regulated, including drug use which may affect this capacity. Thus it is claimed that the employer has the right to test employees for drug use and to impose sanctions when it is discovered., I argue that the implications of the productivity argument lead to unacceptable consequences and thus must be rejected. The productivity argument can be examined in light of a thought-experiment in which the reader is asked to imagine the discovery of two drugs, both of which enhance employee productivity. Calling these drugs “hedonine” and “pononine,” I imagine the first to be pleasurable to the employee while the second is accompanied by a degree of pain and discomfort. Since the mandated use of both of these imagined drugs would be consistent with the productivity argument, I maintain that the productivity argument thereby fails and so must be rejected. As employee drug testing is justified by this argument, it must also be rejected.